Paediatric rehabilitation engineering : from disability to possibility - Chau, Tom; Fairley, Jillian (Boca Raton, Florida : CRC Press, 2011)
"Written by international experts, this book provides an up-to-date synopsis of advances in pediatric rehabilitation engineering research. Offering a single comprehensive resource on the latest research findings, each chapter presents a different area of technology or the developments of particular clinical relevance to pediatric rehabilitation. The material within each chapter also includes a conceptual description of the technology or underlying scientific principles, followed by a synthesis of relevant literature, recent research advances, selected clinical case studies (where applicable), and perspectives for future directions"--Provided by publisher.
chapter 1. Introduction / Tom Chau and Jillian Fairley -- chapter 2. Microswitch-based programs for children and youth with multiple disabilities : an overview of the responses and technology adopted / Giulio E. Lancioni, Nirbhay N. Singh, Mark F. O'Reilly, Jeff Sigafoos, Doretta Oliva and Gabriella Basili -- chapter 3. Access technologies for children and youth with severe motor disabilities / Natasha Alves, Stefanie Blain, Tiago Falk, Brian Leung, Negar Memarian and Tom Chau -- chapter 4. Advances in technologies to support children with communication needs / Gail Teachman and Cynthia Tam -- chapter 5. Optimal web-based survey design in the youth population : enabling access for all / T. Claire Davies and N. Susan Stott -- chapter 6. Paediatric seating / Eric Tam -- chapter 7. Upper and lower extremity prosthetics for children and youth / Elaine Biddiss and Jan Andrysek -- chapter 8. Innovations in robotic devices for autism / Tamie Salter and Francois Michaud -- chapter 9. Virtual reality therapy in paediatric rehabilitation / Patrice L. (Tamar) Weiss, Naomi Weintraub and Yocheved Laufer.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Children with disabilities -- Rehabilitation; Biomedical engineering; Electronic books